p53 protein expression independently predicts outcome in patients with lower-risk myelodysplastic syndromes with del(5q) - Saft, Leonie (Ferrata Storti Foundation, 2014)
Del(5q) myelodysplastic syndromes defined by the International Prognostic Scoring System as low- or intermediate-1-risk (lower-risk) are considered to have an indolent course; however, recent data have identified a subgroup of these patients with more aggressive disease and poorer outcomes. Using deep sequencing technology, we previously demonstrated that 18% of patients with lower-risk del(5q) myelodysplastic syndromes carry TP53 mutated subclones rendering them at higher risk of progression. In this study, bone marrow biopsies from 85 patients treated with lenalidomide in the MDS-004 clinical trial were retrospectively assessed for p53 expression by immunohistochemistry in association with outcome. Strong p53 expression in ≥1% of bone marrow progenitor cells, observed in 35% (30 of 85) of patients, was significantly associated with higher acute myeloid leukemia risk (P=0.0006), shorter overall survival (P=0.0175), and a lower cytogenetic response rate (P=0.009), but not with achievement or duration of 26-week transfusion independence response. In a multivariate analysis, p53-positive immunohistochemistry was the strongest independent predictor of transformation to acute myeloid leukemia (P=0.0035). Pyrosequencing analysis of laser-microdissected cells with strong p53 expression confirmed the TP53 mutation, whereas cells with moderate expression predominantly had wild-type p53. This study validates p53 immunohistochemistry as a strong and clinically useful predictive tool in patients with lower-risk del(5q) myelodysplastic syndromes. This study was based on data from the MDS 004 trial (clinicaltrials.gov identifier: NCT00179621).